Dati e algoritmi. Dal rapporto tra validità ed effettività a una questione antropologico-giuridica (tramite la norma) - Campo, Alessandro (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
This paper focuses on the relationship between law and data (and also algorithms). This relationship is the starting point for developing the issue of sollen through Kelsen, Deleuze and Lacan. The goal is to show a shift from the link between validity and effectiveness in normativism to an anthropological question related to the role of fictionalism in law.